1987
DOI: 10.1007/bf00253970
|View full text |Cite
|
Sign up to set email alerts
|

(2?-R)-4?-o-Tetrahydropyranyladriamycin, a new anthracycline derivative; its effectiveness in lymphoid malignancies

Abstract: Thirty-eight patients with adult acute lymphoblastic leukemia (ALL) or non-Hodgkin's lymphoma (NHL) were treated intravenously with (2"-R)-4'-o-Tetrahydropyranyladriamycin (THP) at a dose of 10 mg/m2 for 5 consecutive days. Seven complete and 15 partial responses were observed in 35 evaluable patients (overall response rate, 62.8%). Both antitumor activity and antitumor spectrum were similar to those for doxorubicin. Since the patients who had had chemotherapy previously, including other kinds of anthracycline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 8 publications
0
22
0
Order By: Relevance
“…THP is a derivative of DOX and is reportedly less cardiotoxic than DOX [3][4][5]. Elderly patients often have cardiac dysfunction, and treatment with anthracyclines frequently has to be discontinued due to cardiotoxic side effects.…”
Section: Haematological Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…THP is a derivative of DOX and is reportedly less cardiotoxic than DOX [3][4][5]. Elderly patients often have cardiac dysfunction, and treatment with anthracyclines frequently has to be discontinued due to cardiotoxic side effects.…”
Section: Haematological Toxicitymentioning
confidence: 99%
“…In particular, anthracyclines, which are regarded as effective for NHL, are difficult to administer because of their cardiotoxicity and myelosuppressive effects. Pirarubicin (tetrahydropyranyl adriamycin: THP), a derivative of doxorubicin (DOX), is a new anthracycline that has been reported to be less cardiotoxic than DOX [3][4][5]. Accordingly, a THP-COP regimen [6] composed of THP, cyclophosphamide (CPA), vincristine (VCR), and prednisolone (PSL) has been administered for the treatment of NHL in elderly patients [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…A greater dose of each drug in VEP-THP (1) or administration schedule of THP might produce the difference. In the previous study [2], we have demonstrated a fairly good re sponse rate by administering 10 mg/'m2 of THP for 5 consecutive days. Experimental data [10] also support the advantage of an administration schedule of frac tionated low doses.…”
Section: Discussionmentioning
confidence: 99%
“…Alopecia induced by ADM is also a troublesome side effect especially for female patients although it is not life-threatening. In phase II study, pirarubicin (THP) has been proved to have almost equivalent antitumor activity and similar antitumor spectrum to ADM [2] with lesser car diotoxicity and much milder alopecia [2,3], Therefore, we intended to substitute ADM by THP in VEPA [4] or CHOP [5] regimen which are common first-line chemotherapy regimens in the treatment of NHL. This is a retrospective analysis of therapeutic results obtained by the combination chemotherapy with THP, cyclophosphamide (CPM), vincristine (VCR), and prednisolone (VEP-THP therapy).…”
Section: Introductionmentioning
confidence: 99%
“…Pirarubicin tetrahydropyranyl adriamycin : THP is an anthracycline derivative of doxorubicin DOX that is reportedly less cardiotoxic than DOX 1,2 . A regimen of THP, cyclophosphamide CPA , vincristine VCR , and prednisolone PSL THP-COP or TCOP has been used to treat Non-Hodgkin lymphoma NHL in elderly patients [3][4][5] ; the Japanese Clinical Study Group of THP Lymphomas in the Elderly JGTLE reported the ef cacy of the same regimen in a large-scale, multicenter trial 5 .…”
Section: Introductionmentioning
confidence: 99%